Hubungan Usia dengan Kejadian Hipotensi Pada Pasien Pasca Spinal Anestesi di Kamar Operasi Rumah Sakit Umum Tgk. Chik Ditiro Sigli Kabupaten Pidie Aceh - Zulfakhrizal Zulfakhrizal; Tri Sumarni; Siti Haniyah (Viva Medika, 2023)
Background : Hypotension is the most common complication during spinal anesthesia with an incidence of more than 80%. Objective: The study aims to determine the relationship between age and the incidence of hypotension in post-spinal anesthesia patients in the operating room of Tgk General Hospital. Chik Ditiro Sigli. Methods: This study uses cross-sectional analytic types. The population in this study were intraoperative patients under spinal anesthesia at Tgk Chik Ditiro Hospital, Pidie District, Aceh Province in the last 2 months, namely 112 patients. The sampling technique in this study used a purposive sampling technique of 88 respondents. Data analysis was performed univariately and bivariately using the chi square test. Results: Most of the post-spinal anesthesia patients were early adults (26-35 years) with 40 respondents (45.5%). The incidence of hypotension in post-spinal anesthesia patients was found that most of them did not experience hypotension as many as 54 respondents (61.4%). There is a significant relationship between age and the incidence of hypotension in post-spinal anesthesia patients with a p-value<0.001.. Conclusion: This study concluded that there is a significant relationship between age and the incidence of hypotension in post-spinal anesthesia patients in the operating room of Tgk General Hospital. Chik Ditiro Sigli.